Mediterranean versus western diet effects on cerebral cortical thickness and volume in cynomolgus macaques: Neuroimaging / animal imaging. (7th December 2020) - Shively, Carol A.; Frye, Brett M.; Register, Thomas C.; Andrews, Rachel N.; Appt, Susan E.; Vitolins, Mara Z.; Uberseder, Beth; Silverstein‐Metzler, Marnie G.; Chen, Haiying; Whitlow, Christopher T.; Barcus, Richard A.; Lockhart, Samuel N.; et al.
Abstract: Background: Associations between diet, cognitive decline and neurodegenerative disease, including Alzheimer's Disease (AD), have been reported, but whether these relationships are causal is difficult to determine in human studies. Cynomolgus macaques ( Macaca fascicularis ), like humans, are omnivorous, have complex central nervous systems, and are susceptible to diet‐induced diseases. Similar to humans, these nonhuman primates accumulate amyloid and tauopathies with age, and diabetes accelerates age‐related amyloid accumulation. Thus, these primates are appropriate models for investigations of diet effects on the brain. Method: Using structural magnetic resonance imaging, we examined diet effects on brain anatomy by measuring the thicknesses and volumes of AD‐signature cortical regions of interest (ROIs) in 38 middle‐aged females, at baseline and after consumption of either a Mediterranean (MED) or Western (WEST) diet for 36 months (∼ equivalent to a 9‐year follow up in humans). Result: Using repeated measures analysis, cortical thicknesses were significantly increased in the WEST diet group in the angular gyrus (p<0.001), inferior temporal gyrus (p<0.001), middle temporal gyrus (p<0.001), superior temporal gyrus (p<0.001), supramarginal gyrus (p<0.001), fusiform gyrus (p<0.01), precuneus (p<0.001), parahippocampal gyrus (p<0.01), and an AD meta‐ROI (p<0.001). WEST diet also resulted in increases in total brain volume (p<0.02) and gray matter (p<0.01) and decreases in cerebrospinal fluid (p<0.01), white matter (p<0.01), and deep gray matter (striatum and thalamus) (p<0.05). In contrast to the patterns observed in the WEST diet group, thicknesses and volumes generally remained unchanged between baseline and 31 months treatment in animals consuming the MED diet. Conclusion: Taken together, these findings demonstrate that WEST diets likely induce widespread structural shifts, which may increase risk of cognitive decline and neuropathology; whereas MED diets may exact a stabilizing influence on the brain. This study provides important insights about the significance of diet on brain structure, and lays the groundwork for future investigations to uncover the molecular underpinnings of diet‐induced changes in the brain.